2015
DOI: 10.1097/hcr.0000000000000112
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Obesity in 2015

Abstract: Obesity is a major health priority in the United States, as well as globally. It is associated with multiple comorbidities and reduced life expectancy. Effective management of obesity involves producing an intervention plan tailored to the individual patient. Potential contributory factors to weight gain, including dietary habits, physical inactivity, associated medical conditions, and medications, should be identified and addressed. Lifestyle interventions comprising diet modification, physical activity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 80 publications
0
31
0
1
Order By: Relevance
“…8 Side effects of phentermine include tachycar- dia, hypertension, dry mouth, anxiety, insomnia and constipation. 1 Kim et al did a post marketing surveillance study on 837 obese patients on phentermine, and this revealed a 30% incidence rate of adverse effects. The three most common side effects were insomnia (11.4%), dry mouth (5.9%), and dizziness (2.7%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8 Side effects of phentermine include tachycar- dia, hypertension, dry mouth, anxiety, insomnia and constipation. 1 Kim et al did a post marketing surveillance study on 837 obese patients on phentermine, and this revealed a 30% incidence rate of adverse effects. The three most common side effects were insomnia (11.4%), dry mouth (5.9%), and dizziness (2.7%).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Later in 2012, phentermine/ topiramate was approved by the FDA and became the first combination drug for long-term management of obesity. 1 Data from meta-analysis showed that patients taking phentermine lost 3.6 kg (CI, 0.6-6.0 kg) on average compared with placebo. 8 Side effects of phentermine include tachycar- dia, hypertension, dry mouth, anxiety, insomnia and constipation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Подавляя активность желудочно-кишечных липаз, орлистат уменьшает всасывание жиров, вызывая дефицит энергии и снижение массы тела. А также, уменьшая количество свободных жирных кислот и моноглице-ридов в просвете кишечника, уменьшает раствори-мость и всасывание холестерина и снижает гиперхо-лестеринемию [10][11][12].…”
unclassified